Evaluation of anifrolumab safety in systemic lupus erythematosus: A meta-analysis and systematic review - Liu, Zhihui; Cheng, Ruijuan; Liu, Yi (Frontiers in Immunology, 2022)
Objectives Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, and type I interferon plays an important role in its pathogenesis. Anifrolumab is a new strategy for the treatment of systemic lupus erythematosus. It could antagonize the activity of all type 1 interferons by binding with type I interferon receptor subunit 1. The aim of our study was to evaluate the safety of anifrolumab in patients with moderate to severe SLE (excluding patients with active severe lupus nephritis or central nervous system lupus). Methods Four databases (Embase, Cochrane, PubMed, Web of Science) were systematically searched from inception until December 2021 for randomized controlled trials (RCTs) evaluating the safety of anifrolumab versus placebo in SLE patients. Then, the incidence of adverse events in each study was aggregated using meta-analysis. Results A total of 1160 SLE patients from four RCTs were included in the analysis. Serious adverse events were less common in the anifrolumab group than in the placebo group (RR: 0.76, 95% CI: 0.59-0.98, p<0.03). The most common adverse events included upper respiratory tract infection (RR: 1.48, 95% CI: 1.13-1.94, P=0.004), nasopharyngitis (RR: 1.66, 95% CI: 1.25-2.20, P=0.0004), bronchitis (RR: 1.96, 95% CI: 1.32-2.92, P=0.0009), and herpes zoster (RR: 3.40, 95% CI: 1.90-6.07, P<0.0001). Conclusion Anifrolumab is considered a well-tolerated option for the treatment of SLE patients with good safety. Key words Systemic lupus erythematosus, type I interferon, anifrolumab, RCTs, meta-analysis